2012
DOI: 10.1371/journal.pone.0048396
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum Depression and Anxiety Associated with Disability in African Women: Cross-Sectional Results from the CDS Study in Ghana and Côte d'Ivoire

Abstract: BackgroundCommon mental disorders, particularly unipolar depressive disorders, rank among the top 5 with respect to the global burden of disease. As a major public health concern, antepartum depression and anxiety not only affects the individual woman, but also her offspring. Data on the prevalence of common mental disorders in pregnant women in sub-Saharan Africa are scarce. We provide results from Ghana and Côte d'Ivoire.MethodsWe subsequently recruited and screened n = 1030 women in the third trimester of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 35 publications
5
60
4
3
Order By: Relevance
“…Numerous studies on CPMD have found that a history of mental health disorders increases the risk for current diagnoses and that depression and anxiety are commonly comorbid in the perinatal period (Heron et al 2004; Littleton et al 2007; Teixeira et al 2009; Field et al 2010; Matthey and Ross-Hamid 2012; Bindt et al 2012). Where depression and anxiety disorders occur simultaneously, the deleterious effects on maternal and child well-being may be compounded: symptoms may be more severe, duration of episodes of either disorder may be longer and have a chronic course, there may be worse impairment of maternal functioning, a poorer response to treatment and increased suicidality (Field et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on CPMD have found that a history of mental health disorders increases the risk for current diagnoses and that depression and anxiety are commonly comorbid in the perinatal period (Heron et al 2004; Littleton et al 2007; Teixeira et al 2009; Field et al 2010; Matthey and Ross-Hamid 2012; Bindt et al 2012). Where depression and anxiety disorders occur simultaneously, the deleterious effects on maternal and child well-being may be compounded: symptoms may be more severe, duration of episodes of either disorder may be longer and have a chronic course, there may be worse impairment of maternal functioning, a poorer response to treatment and increased suicidality (Field et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Les éléments de mise en oeuvre du projet ont déjà été décrits (Bindt et al, 2012). L'étude s'est déroulée de février 2010 à décembre 2011 à l'Hôpital Général d'Abobo Nord et au Laboratoire de Biologie de l'Institut National de la Santé Publique (INSP) d'Abidjan pour l'analyse des échantillons.…”
Section: Materiel Et Methodes Cadre Type Et Période De L'étudeunclassified
“…La thrombopénie a été retrouvée respectivement chez 34,4% de nouveau-nés de mères déprimées et 26,6% de ceux nés de mères non déprimées, ainsi qu'une thrombocytose (3,1 versus 4,7%) (Tableaux 4, 5 et 6). (Bindt et al, 2012 ;Hartley et al, 2011 ;Adewuya et al, 2007). Les études ont également montré l'impact de la dépression maternelle sur le développement de l'enfant ainsi que la santé de la mère.…”
Section: Relationunclassified
See 1 more Smart Citation
“…1, 1113 In western Africa, children of depressed mothers have been found to have elevated risk of morbidity and mortality as compared to those of non-depressed mothers. 21, 22 Despite this, most studies have not evaluated the effects of ECD interventions on the mental health of the child’s mother or caregiver. 6 …”
Section: Introductionmentioning
confidence: 99%